Influence of ultrasound on forming force in thin sheetmetal microforming using molten plastic as flexible punch - Rui-xiang Yang (Elsevier, 2021)
In this paper, a measuring force method was proposed for a special ultrasonic microforming method -- Micro Ultrasonic thin Sheetmetal Forming using molten plastic as flexible punch (short as Micro-USF), and the unique force change law in Micro-USF was observed. Using a flexible punch of the methyl silicone oil in the contrast experiment, the influence of ultrasound on the forming force in Micro-USF was investigated. The force transfer properties of the methyl silicone oil and molten EVA were analyzed (the molten EVA is a flexible punch used in Micro-USF). Experiment results showed that the ultrasound could significantly decrease the forming force in Micro-USF. Compared with the contrast experiment, the forming force in Micro-USF could be decreased by 74.7% and 91.0% respectively under the pre-pressure force of 196 N and 98 N when an arc-shape cross section microchannel with an opening width 755.1 μm and depth 247.8 μm was formed for an annealed copper sheet with a thickness of 30 μm.